Druze Reincarnation Narratives Previous Life Memories, Discourses, and the Construction of Identities - Fartacek, Gebhard (Peter Lang International Academic Publishing Group, 2021)
"This book follows the journey of Druze individuals who can remember their former lives and go on search for their previous families. For the Druze, an ethno-religious minority in the Middle East split between different nation-states, such cases and related discourses embody ambivalent bridges between personal, familial, and ethnic identities. The contributions in this book, presented by Eléonore Armanet, Nour Farra Haddad, Gebhard Fartacek, Tobias Lang, Lorenz Nigst, and Salma Samaha, draw on ethnographic inquiries and illuminate the broad field of Druze conceptions of rebirth and group coherence against the backdrop of everyday challenges and recent conflicts in the Middle East and beyond."